Experimental and numerical studies on the performance of light gauge steel-concrete composite channel section beams - Ipe, T. Valsa; Bai, H. Sharada (Journal of Structural Engineering, 2024)
Experimental studies are carried out to investigate the performance of light gauge steel-concrete composite channel section beams having different depth to thickness ratios and compared with that of non-composite channel section beams. FEM analysis using ANSYS is carried out to develop a numerical model to study the nonlinear behaviour of composite beams and a comparative study between experimental and numerical results is also carried out. Ultimate loads obtained from the FE analysis for composite beams are found to be close to the experimental results. Experimental investigation reveals that limiting the flat width ratio to 60 when simple lip is provided, as recommended by codes of practice for non-composite beams, is not a barrier for composite beams.